Theory Matters
XII, 362 p.
Keywords: This book demonstrates that theory in literary and cultural studies has moved beyond overarching master theories towards a greater awareness of particularity and contingency – including its own. What is the place of literary and cultural theory after the Age of Theory has ended? Grouping its chapters into rubrics of metatheory, cultural theory, critical theory and textual theory, the collection demonstrates that the practice of “doing theory” has neither lost its vitality nor can it be in any way dispensable. Current directions covered include the renewed interest in phenomenology, the increased acknowledgement of the importance of media history for all cultural practices and formations, complexity studies, new narratology, literary ethics, cultural ecology, and an intensified interest in textual as well as cultural matter.